RUBEE IMMERSION: VIRTUAL REALITY-BASED DIABETES EDUCATION MEDIA RUBEE SLIDE-TABS - Fakhri, Muhammad Zhafran; Yuliska, Siti Syarah; Pranoto, Rania Gantari; Afryansyah (Jurnal Informatika Teknologi dan Sains (Jinteks), 2025)
Diabetes Mellitus is a chronic disease with a prevalence that continues to increase every year, so effective educational efforts are needed to improve public understanding. This research developed Rubee Immersion, a Virtual Reality (VR)-based health education and literacy media that aims to provide an interactive understanding of the causes, symptoms, and management of diabetes. Apart from being a means of education, this media also functions as a means of dissemination to introduce Rubee-Dia Tabs, herbal products made from Brucea javanica and forest honey which have the potential to help manage blood sugar levels. With a VR technology approach, Rubee Immersion is expected to be able to increase public awareness, knowledge, and interest in treating diabetes naturally and preventively.